Majelis Percikan Iman: Building Harmony in the Heterogeneity of Religious Organizations in Bandung City - Saepudin, Juju (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This article presents the results of research on the role of Majelis Percikan Iman (MPI) in building harmony in the heterogeneity of religious organizations in Bandung city. This theme was important to study because there were many frictions between majelis taklim due to differences in ideas and views. This research was conducted with a descriptive qualitative approach. Data collection was done by interviewing, observing, and studying literature on various documents related to the research theme. Based on the results of the inductive analysis, some conclusions could be drawn as follows: First, the model of Ustadz Aam Amirudin's delivery which was friendly, relaxed and did not impeach certain groups in the learning process was the main attraction for MPI members from various ages and religious organizations. Second, various answers given by Ustadz Aam Amirudin in the question-and-answer session always provided alternatives in every problem, but remain decisive and clear, so that it brought a coziness for the participants. Third, MPI opened up opportunities for other Dai from Nahdhatul Ulama, Persatuan Islam, Muhammadiyah, Persatuan Umat Islam, and other religious organizations or academic practitioners to be speakers in order to create mutual support to educate the people, so that harmony was established in the heterogeneity of religiosity. Fourth, MPI is present to integrate religious values with culture and local wisdom that are implemented through the da'wah model by promoting the spirit of harmony.